Saberes docentes e conhecimentos discentes sobre o Sistema Cifranávico no 1º ano do ensino fundamental - Sampaio, Aline Rodrigues (2018)
The learning of the called Decimal Number System – DNS is essential for student´s progression in the arithmetic field. Currently, the teaching of DNS happens by rules and with a little use of didactic resources, which does not favor the student’s comprehension about its characteristics and its operation. The student’s numerical records expresses their knowledge about the DSN, which needs to be interpreted by the teacher. Nacarato (2009) postulates that it is not enough that the Math’s teacher in the initial years of the elementary School gets the pedagogical knowledge. In this way, Pimenta (1996) and Tardif (2002) point the necessity that the teacher develop the knowledge about what the teacher is going to teach: content’s knowledge (BARGUIL, 2016b). Because of that, it is necessary that the teachers have an appropriate training to prosecute this job. This research has as general objective expand teacher knowledge – contente, pedagogical and existential – about the DSN named by Barguil (2016a) as Ciphernavic System – CS, written by a teacher who teaches at the first grade of the elementary School. The specific objectives are: i) to know the didactic strategies used by the teachers in the SC teaching of the CS; and ii) map the student’s knowledge about the SC. The qualitative research was carried out with a teacher and 9 (nine) students from the 1st year of Elementary School, from the public system of Fortaleza. The methodology of analysis consisted in one direct observation in loco of pedagogical practices, semi-structured interview to identify the teaching knowledge about CS and application of a numerical knowledge diagnosis to identify students' cipher and reading skills. The results of this research reveal that the teacher does not have the necessary knowledge about CS, which are relevant for proposing practices that favor both literacy and ciphernavaring, taking into account that in both systems it is necessary to use resources and practices pedagogical skills that value orality – listening and speaking – and the recording, notation – reading and writing. In relation to the students' knowledge about the SC, this research revealed that the students have quite different knowledge, considering the amount of correctness and errors, as well as the types of these. This complex scenario is ignored by the teacher, since she does not develop assessment on ciphernavaring, contrary to what happens in relation to literacy, which is evaluated periodically.